(untitled) (The Research of Medical Science Review, 2025)
Introduction: Warts are the predominant cutaneous manifestation of human papillomavirus (HPV), which infects both dermal and mucosal epithelial tissues. The management of warts is difficult. The viral etiology of warts indicates that acyclovir, an antiviral agent effective against DNA viruses, could serve as a viable therapeutic alternative. Objective: To determine the response of intralesional acyclovir in patient presenting with plantar warts. Methodology: This descriptive study was performed in the Department of Dermatology, Tertiary care hospital, Karachi from 2nd July to 2nd Jan 2025. Total 175 male and female patients of age between 18 to 65 years, exhibiting plantar warts, regardless of duration. Informed consent was taken from the patient after explaining risk and benefits of the study. Patients were administered intralesional acyclovir (70 mg/ml; Acyclovir), with 0.1 mL injected into the base of each wart every 02 weekly for a maximum of six sessions (at 0, 2, 4, 6, 8, and 12 weeks). The treatment response was evaluated at 12 weeks and classified as: Complete reaction (total eradication of warts or >75% improvement); Partial response (50-75% decreased quantity/size but not entire elimination); No response (<50% or no diminution of lesions). Statistical analysis was conducted utilizing SPSS version 24. Result: In this study male and female ratio was 1:1; while females were 50.29% (n=88/175) of study population. Cumulative mean age of the study patients was 39.20 ± 11.47 years. 77 (44.0%) patients had complete response, 68 (38.86%) had partial response and 30 (17.14%) had no response. A Statistically significant difference was noticed only for age groups and residential status among all the study confounders. Conclusion: The treatment proved beneficial in the majority of cases, with age and residential status served as strong predictors of response. These findings enhance the existing knowledge on plantar warts care and highlighted the necessity for more studies to refine treatment options.